Readiness of 12th-Grade Students in Senior High Schools in Bekasi City in SNBT English Literacy (Lembaga Pengembangan Kinerja Dosen, 2025)
The readiness of students in facing the National Selection Based on Tests (SNBT) is an important factor in determining success in entering higher education, especially in the area of English literacy, which is part of the exam. This study aims to analyze the readiness of 12th-grade students in senior high schools across Bekasi City in facing the SNBT, with a focus on English literacy. The research method used is descriptive survey, in which data were collected through a Google Form-based questionnaire filled out by 25 students of class 12. The results show that the majority of respondents have a good basic understanding of English literacy, but there are still shortcomings in aspects of understanding complex texts and using effective reading strategies. In addition, 60% of students feel confident in their abilities, while 40% indicate the need for additional training to improve readiness. Factors such as the frequency of practice questions and access to English-language learning materials have a significant impact on the students' level of readiness. This study recommends the implementation of an intensive learning program and practice questions based on English literacy to improve students' abilities in facing the SNBT. By understanding students' readiness comprehensively, educational institutions can design more effective learning strategies.